Korelasi Kualitas Tidur Dengan Tingkat Stres Dan Tingkat Depresi Orang Tanpa Gejala Covid 19 - Liliek Pratiwi; Yane Liswanti; Harnanik Nawangsari (Universitas Malahayati Lampung, 2022)
ABSTRACT The Covid-19 virus infection is currently a worldwide concern. With the rapid spread of this virus infection and the addition of cases every day in Indonesia, it will be a double burden for the health system and the welfare of society in general. The data obtained from the Covid 19 Handling Committee and National Economic Recovery, as of December 15, 2020, a total of 623,309 were confirmed positive with 5,489 cases. DKI Jakarta Province occupies the first position, with 152,499 cases. Based on data from the DKI Jakarta Provincial Health Office, as of October 1, 2020, 53% of Covid's 19 patients were OTG (People Without Symptoms). The impact of this increase in OTG, namely that several isolation places have been prepared by the government, it could be added, then, these OTG patients who are certainly separated from their families, are hampered in working, many experience stress and feelings of helplessness, which in turn can reduce the quality of life. Covid-19 patient life. Of the 27 patients, 15 COVID-19 patients with OTG complained of feeling anxious away from their families, feeling dizzy about continuing their work, and often crying alone because they thought about themselves and their families. To determine the correlation of sleep quality with stress levels, and depression levels of people without COVID-19 symptoms in DKI Jakarta. This study used an analytic survey method, with a total of 52 COVID-19 patients with OTG as respondents. Data analysis using Spearman test correlation. The research instrument used the Pittsburgh Sleep Quality Index (PSQI), and the Depression Anxiety Stress Disorder Scale (DASS) questionnaire. There is a correlation between sleep quality and stress levels, and depression levels in people without symptoms of Covid 19 patients in DKI Jakarta. The results of statistical analysis of the correlation of sleep quality with stress levels(r=0,33;p0,001), correlation of sleep quality with depression level (r=0,35; p0,001). The conclusion of the study is that the disease process in OTG that has an impact on sleep quality is related to the psychological condition of the patient. Keywords: Sleep Quality, Stress Level, Depression Level, People Without Symptoms ABSTRAK Infeksi virus Covid 19 saat ini menjadi perhatian dunia. Dengan cepatnya penyebaran infeksi virus ini dan penambahan kasus setiap harinya di Indonesia, akan menjadi beban ganda bagi sistem kesehatan dann kesejahteraan masyarakat pada umumnya. Data yang didapatkan bersumber dari Komite Penanganan Covid 19 dan Pemulihan Ekonomi Nasional, per tanggal 15 Desember 2020, sejumlah 623.309 terkonfirmasi positif dengan 5.489 kasus. Provinsi DKI Jakarta menduduki posisi pertama, dengan jumlah kasus 152.499. Dari data Dinas Kesehatan Pemprov DKI Jakarta, per tanggal 1 Oktober 2020, 53% pasien Covid 19 merupakan OTG (Orang Tanpa Gejala). Dampak dengan meningkatnya OTG ini, yaitu beberapa tempat isolasi sudah banyak disiapkan oleh pemerintah, bisa jadi ditambah, kemudian, pasien OTG tersebut yang tentunya terpisah dari keluarga, terhambat dalam bekerja, banyak yang mengalami stres dan perasaan tidak berdaya, yang pada akhirnya bisa menurunkan kualitas hidup pasien covid 19. Dari 27 pasien, 15 pasien covid 19 dengan OTG mengeluh merasa cemas jauh di keluarga, merasa pusing mengenai kelanjutan pekerjaanya, dan sering menangis sendiri karena memikirkan keadaan dirinya dan keluarganya. Tujuan untuk mengetahui korelasi kualitas tidur dengan tingkat stres, tingkat depresi Orang Tanpa Gejala covid 19 di DKI Jakarta. Penelitian ini menggunakan metode survei analitik, dengan jumlah responden 52 pasien covid 19 dengan OTG. Analisis data menggunakan korelasi spearman test. Instrumen penelitian menggunakan Pittsburgh Sleep Quality Index (PSQI), kuesioner Depression Anxiety Stress Disorder Scale (DASS). Terdapat korelasi kualitas tidur dengan tingkat stres, tingkat depresi Orang Tanpa Gejala Pasien Covid 19 di DKI Jakarta. Hasil analisis statistik korelasi kualitas tidur dengan tingkat stres (r=0,33;p0,001), korelasi kualitas tidur dengan tingkat depresi (r=0,35; p0,001). Kesimpulan penelitian yaitu proses penyakit pada OTG yang berdampak pada kualitas tidur berhubungan dengan kondisi psikologis pasien. Kata Kunci: Kualitas Tidur, Tingkat Stres, Tingkat Depresi, Orang Tanpa Gejala